A new perspective on the internal structure of polyacrylonitrile-based preoxidized fibers through ultrathin sections. (September 2019) - Wang, Wenli; Wang, Chengguo; Gao, Quan; Chen, Meiling; Wang, Yanxiang; Yao, Zhiqiang
Abstract: The dry-jet wet spinning polyacrylonitrile fibers (PAN fibers) were preoxidized in six gradient-elevated temperature zones and the internal structure changed greatly. Ultrathin sections for electron microscopy were used to study the internal structure of the fibers, and the fibril structure in the fibers was first observed by ultrasonic etching under a high-resolution transmission microscope. The fibers were ultrasonically etched in dimethyl sulfoxide (DMSO) solution to separate the fibril structure. The fibril structure is parallel to the fiber axis and the lamellar-plate structure is arranged perpendicular to the fiber axis. Highlights: Ultrathin sections of preoxidized fibers with a thickness of about 70 nm were prepared by ultrathin sectioning technique. Ultrathin sections of preoxidized fibers were etched in DMSO solution and observed under HRTEM. The lamellar structure perpendicular to the fiber axis and the fibril structure parallel to the fiber axis were observed.